End of Covid-19 Insolvency Emergency Measures in Post-Soviet Countries (London Journal of Research In Humanities and Social Sciences, 2024)
This study focuses primarily on the scope of measures that have helped national governments withstand the destructive consequences of the COVID-19 pandemic and save domestic businesses from bankruptcy. The aspect is explored from the point of view of employee rights in insolvency. Looking back over the insolvency situation in the pandemic period, the unprecedented measures of national governments that inhibit the significant growth of bankruptcies were discussed. The review of crisis measures has highlighted that, once temporary emergency measures conclude, countries will still require effective insolvency protecting workers rights to manage the resulting employee debt burden.
Keywords: COVID-19 pandemic; insolvency; wage claims.